The Development of Bicycle Mobility in Gdańsk And Its Importance In The Face of The Covid 19 Pandemic - Marzena WANAGOS (Communications of International Proceedings, 2021)
The bicycle is a means of transport which in many studies is indicated as the future of city transport. For many years, it has become a priority in development policy also in many European cities, e.g. in the Netherlands, Denmark or Germany, as well as in Italy, France and Great Britain. Cycling in cities is in line with the trends of sustainable development and a healthy lifestyle. For many, it is also an expression of improving the quality of life. In the face of the Covid 19 pandemic, cycling mobility has become even more important. Such transport allows you to avoid direct proximity to people. So it increases security. In this study, Gdańsk is an example of an analysis of city management in favor of bicycle mobility in relation to the situation of the Covid 19 pandemic. The study aims to present selected aspects relating to the city's long-term policy. The aim was also to show the views of bicycle users on the city's policy in this regard in the context of the Covid 19 pandemic. The research problem results from the fact that the behavior of city dwellers changed during the time of Covid 19 and the requirements for bicycle mobility increased significantly. In the face of a marked increase in bicycle mobility in the city, do the inhabitants appreciate the existing conditions for the use of bicycles as a means of transport?  Do they prefer this measure because of safety in the wake of the Covid 19 pandemic?
Keywords: Bicycle Mobility; City Bicycle Infrastructure; Bicycle Transport In The Pandemic.